PENINGKATAN KETERAMPILAN MENULIS PANTUN DENGAN MODEL THINK TALK WRITE PADA SISWA KELAS V SD - Widodo, Bayu; Sumartiningsih, Sri; Yuwono, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses a classroom action research method with data collection techniques in the form of tests and non-tests (observations). The analysis technique uses quantitative descriptive. This research aims to improve the skills of class V-B students in writing rhymes. The results in class V-B, the average score of class V-B students in the cycle I rhyme writing test reached 69.4% with sufficient criteria. Meanwhile, the average score for class V-B students in cycle II reached 82.96% with Good criteria. The completion rate in cycle I still reached 40.7%. In cycle II, the completion rate in cycle II reached 85.2%.